Comparison of self-adhesive taping and short-leg casting to treat tuberosity fractures of the proximal fifth metatarsal: A prospective study - Batıbay, Sefa; Bayram, Serkan; Duman, Sedat; Karaytuğ, Kayahan; Çamur, Savaş (NLM (Medline), 2022)
BACKGROUND: The aim of this study is to compare clinical and radiologic outcomes of self-adhesive taping (SAT) or a short- leg cast (SLC) groups with base of fifth metatarsi. METHODS: Functional outcome was assessed by the Visual-Analogue-Scale Foot and Ankle (VAS-FA) at the Emergency and at 2, 4, 6, and 12 weeks. Labour loss, bone union and The American Orthopedic Foot and Ankle Score (AOFAS) at 12 weeks were also assessed. RESULTS: There was no difference between the SAT group and SLC group in VAS-FA scores at time of injury, 6 and 12 weeks. The SAT group had a significantly higher mean VAS-FA score at the second and fourth weeks of follow-up compared with the SLC group (P = .001 and P = .039, respectively). No correlation was observed between the fracture gap and functional scores for both groups. There was no difference in AOFAS between two groups at 12 weeks. Twenty one patients were unable to work for a mean of 38.2 days during the treatment. 10 patients with the SAT missed 37.5 days and eleven patients with the SLC g missed 40.2 (p: 0.41). The bone union was also achieved for all patients within 12 weeks. CONCLUSION: Treatment with SAT in these fractures had satisfactory functional results compared with traditional SLC. Although there were no significant differences in labor loss and use of assistive devices, The VAS-FA score was significantly higher in SAT group than the SLC group at the second and fourth weeks of treatment.
Keywords: Metatarsal; Tuberosity Fractures; Self-Adhesive Taping